Signatures of Ultrarelativistic Electron Loss in the Heart of the Outer Radiation Belt Measured by Van Allen Probes. Issue 10 (17th October 2017) - Aseev, N. A.; Shprits, Y. Y.; Drozdov, A. Y.; Kellerman, A. C.; Usanova, M. E.; Wang, D.; Zhelavskaya, I. S.
Abstract: Up until recently, signatures of the ultrarelativistic electron loss driven by electromagnetic ion cyclotron (EMIC) waves in the Earth's outer radiation belt have been limited to direct or indirect measurements of electron precipitation or the narrowing of normalized pitch angle distributions in the heart of the belt. In this study, we demonstrate additional observational evidence of ultrarelativistic electron loss that can be driven by resonant interaction with EMIC waves. We analyzed the profiles derived from Van Allen Probe particle data as a function of time and three adiabatic invariants between 9 October and 29 November 2012. New local minimums in the profiles are accompanied by the narrowing of normalized pitch angle distributions and ground‐based detection of EMIC waves. Such a correlation may be indicative of ultrarelativistic electron precipitation into the Earth's atmosphere caused by resonance with EMIC waves. Key Points: Formation of local minimums in phase space density profiles of ultrarelativistic electrons coincides with EMIC wave occurrence New local minimums are accompanied by narrowing of normalized pitch angle distributions The local minimums are indicative of EMIC wave‐induced loss in the heart of the outer belt